فعالية التلقيح المفتوح في تحسين نسبة العقد لبعض أصناف الزيتون المزروعة تحت ظروف الساحل السوري - مهنا, محمد أحمد; دواي, فيصل; القيم, فاضل (Latakia University Journal -Biological Sciences Series, 2014)
أجري البحث في عام 2013 في منطقة بوقا-محافظة اللاذقية, لتبيان فعالية التلقيح المفتوح في تحسين نسبة عقد الثمار مقارنة بالتلقيح الذاتي لخمسة أصناف من الزيتون (خضيري, صوراني أبوشوكة , بيشولين فرنسي , فرنتويو, ليكينو) وذلك لمعرفة أهمية زراعة أصناف ملقحة ضمن حقول الزيتون وحيدة الصنف. أظهرت النتائج تفوق نسبة العقد الأولي والنهائي في شهر حزيران بالتلقيح المفتوح على التلقيح الذاتي. وجد أن الارتباط بين جنس الزهرة ونسبة العقد الأولي كان أعلى في حالة التلقيح الذاتي مقارنة بالمفتوح مما يشير للدور الذي يلعبه الصنف الملقح في تحديد نسبة العقد. تفوق معدّل تساقط الثمار بالتلقيح الذاتي على التلقيح المفتوح في الصنفين "بيشولين فرنسي" و"صوراني أبوشوكة", كما زاد التلقيح الذاتي من نسبة الثمار الصغيرة غير المخصبة التي اقتصر وجودها على الصنفين "خضيري" و "فرنتويو" . أظهر التلقيح المفتوح فعالية نهائية عالية في تحسين الإنتاج وصلت إلى حوالي 11 ضعف التلقيح الذاتي في الصنف "بيشولين فرنسي" وبلغت ما يقارب خمسة أضعاف في حالة الصنف "خضيري" و "صوراني أبوشوكة". تشير نتائجنا إلى أهمية زراعة أكثر من صنف ضمن حقول الزيتون وحيدة الصنف لضمان التلقيح المناسب والإنتاج الأفضل كون التلقيح المفتوح قد أظهر فعالية معنوية في تحسين العقد للأصناف المدروسة. The research was conducted to investigate the efficiency of open pollination in improving fruit set of five olive cultivars (Khodairi, Picholine Languedoc, Sourani Abo-shauke, Leccino and Frantoio), and the importance of planting pollinator cultivars in mono-cultivar olive orchards. The study was carried out at Bouqa/Latakia in the growing season of 2013. The results showed the superiority in the initial and final fruit set obtained by open-pollination over that obtained by self-pollination. The correlation between the flower sex and the initial fruit set was higher in the case of self-pollination, which shows the role of pollinator cultivar in determining the fruit set. The drop Ratio which resulted from self-pollination was superior to that resulted from open-pollination in "Picholine languedoc" and "Khodairi". Also the small (unfertilized) fruit ratio (found only in "Khodairi" and "Frantoio") was higher in the case of self-pollination compared to open pollination. Open-pollination showed higher final efficiency in increasing production; 11 times higher in "Picholine languedoc", and 5 times higher in "Khodairi "and "Sourani Abo-Shauke" compared to self-pollination. Our results show the importance of planting more than one cultivar in olive orchards to obtain adequate pollination and better productivity. This is because open-pollination showed significant efficiency in improving the fruit set of the studied cultivars.